Antibacterial polyethylene composite material

By mixing polyethylene with maleic anhydride grafted polyethylene, composite antibacterial filler and furyl silicone rubber and other materials, an antibacterial polyethylene composite material was prepared, which solved the problem of general mechanical properties, no antibacterial and insufficient anti-corrosion properties of ordinary polyethylene materials, and achieved excellent antibacterial, corrosion-resistant, wear-resistant and hydrophobic properties of the material, and was suitable for a variety of high-demand application scenarios.

CN119661922AInactive Publication Date: 2025-03-21SUZHOU JIADU TEXTILE TECHNOLOGY CO LTD

Patent Information

Application Number
CN202510067422.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Ordinary polyethylene materials have average mechanical properties, no antibacterial effects, and have poor corrosion resistance.

Method used

An antibacterial polyethylene composite material is prepared by mixing polyethylene with maleic anhydride grafted polyethylene, composite antibacterial filler, furyl silicone rubber and other materials. In this composite material, the composite antibacterial filler significantly enhances the antibacterial properties through the synergistic effect of silver-carrying talc powder and chlorogenic acid; furyl silicone rubber enhances the corrosion resistance and hydrophobic properties of the material by modifying the interaction between the hydroxyl group in the silicone rubber structure and the matrix of the polyethylene composite material.

Benefits of technology

The prepared antibacterial polyethylene composite materials not only have excellent antibacterial effects, corrosion resistance, wear resistance and toughness, but also have good hydrophobic ability, which can effectively prevent bacterial erosion, meet the needs of medical devices and food packaging, and have a long service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661922A_ABST
    Figure CN119661922A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, and discloses an antibacterial polyethylene composite material which comprises the following raw materials: polyethylene, maleic anhydride grafted polyethylene, a composite antibacterial filler, furyl silicone rubber, an antioxidant, an ultraviolet light absorber, a plasticizer, a stabilizer and a lubricant. The composite antibacterial filler and the furyl silicone rubber are prepared to participate in the preparation process of the polyethylene composite material, so that the prepared polyethylene composite material has excellent antibacterial effect, corrosion resistance, wear resistance and toughness, also has a good hydrophobic effect, can effectively prevent bacterial erosion, and has a good antibacterial effect. The use requirements in the fields of medical instruments, food packaging and the like are met, and the service life is long.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to an antibacterial polyethylene composite material. Background Art

[0002] Polyethylene material is a thermoplastic polymer material with polyethylene resin as the main body. It has excellent physical and chemical properties and is widely used in many fields such as construction, transportation, national defense, aerospace, medical equipment and food packaging. However, ordinary polyethylene materials have poor corrosion resistance and mechanical properties generally do not have antibacterial properties, making it difficult to meet the use requirements of many fields. Therefore, polyethylene composite materials formed by using polyethylene resin as the main component and adding various additives, fillers, etc. to it came into being.

[0003] The patent with publication number CN101948583B discloses a cross-linked polyethylene composite material and a preparation method thereof, wherein a lubricating and wear-resistant agent, a thermal conductive agent, a cross-linking agent and a first part of ultra-high molecular weight polyethylene are mixed to obtain a masterbatch, the masterbatch is mixed with a second part of ultra-high molecular weight polyethylene to obtain a polyethylene composition, the polyethylene composition is molded, and a cross-linked polyethylene composite material is obtained after demolding. The cross-linked polyethylene composite material prepared by the patent has good self-lubricity, wear resistance, creep resistance, load-bearing capacity and thermal conductivity, and will not cause plastic deformation and bring safety hazards when used for high-speed railway bridge bearings, and has good use effect. However, the polyethylene composite material prepared by the patent has general anti-corrosion ability, and a variety of inorganic substances are directly added thereto. In the process of preparing the composite material, agglomeration of nanoparticles may occur, thereby affecting the performance of the composite material. Summary of the invention

[0004] The purpose of the present invention is to provide an antibacterial polyethylene composite material, which solves the problem that ordinary polyethylene materials have general mechanical properties, no antibacterial effect and poor anti-corrosion performance.

[0005] The purpose of the present invention can be achieved by the following technical solutions: An antibacterial polyethylene composite material comprises the following raw materials in parts by weight: 60-80 parts of polyethylene, 20-25 parts of maleic anhydride grafted polyethylene, 8-10 parts of composite antibacterial filler, 12-15 parts of furan-based silicone rubber, 2-3 parts of antioxidant, 1-2 parts of ultraviolet absorber, 1-3 parts of plasticizer, 2-4 parts of stabilizer and 3-5 parts of lubricant.

[0006] Furthermore, the antioxidant is any one of antioxidant 1010, antioxidant 1135, and antioxidant 5057; the ultraviolet absorber is any one of ultraviolet absorber UV-1577, ultraviolet absorber 1130, and ultraviolet absorber UV-2908; the plasticizer is any one of diisononyl phthalate, dioctyl phthalate, dimethyl phthalate, and epoxy soybean oil; the stabilizer is any one of calcium zinc stabilizer and barium zinc stabilizer; the lubricant is any one of paraffin and polyethylene wax.

[0007] Furthermore, the preparation method of the composite antibacterial filler comprises the following steps: S1: talcum powder is mixed with silver nitrate solution, ultrasonically dispersed for 10-15 minutes, placed in a reaction kettle, heated to 75-85°C, stirred for 6-8 hours, centrifuged to separate the solid, washed and dried to obtain silver-loaded talcum powder; S2: silver-loaded talc powder is placed in toluene, mixed thoroughly, and then chlorogenic acid is added. The mixture is heated and stirred, filtered, washed, and dried to obtain a composite antibacterial filler.

[0008] In this scheme, talcum powder is immersed in a silver nitrate solution, and silver ions are fixed between talcum powder layers by adsorption and ion exchange to obtain silver-loaded talcum powder, and then a composite antibacterial filler is obtained by the interaction between the hydroxyl groups on the surface of the talcum powder and the carboxyl groups in the chlorogenic acid structure. The composite antibacterial filler has multiple active hydroxyl groups on its surface, which can participate in the preparation process of the composite material and has excellent compatibility with the composite material matrix, so that the composite antibacterial filler can be evenly distributed in the composite material, significantly enhancing the wear resistance of the polyethylene composite material, and forming an inorganic-organic synergistic antibacterial agent through the silver ions loaded between its layers and the chlorogenic acid modified on its surface, and the silver ions can interfere with the bacterial cell wall and protein The synthesis of protein can be induced by chlorogenic acid, which can induce bacterial death. Chlorogenic acid can inhibit the arylamine acetyltransferase in bacteria through non-competitive inhibition, thereby causing bacterial metabolic disorders, inhibiting bacterial growth and reproduction, and interfering with the synthesis of bacterial nucleic acids, thereby achieving excellent antibacterial effects. The synergistic antibacterial effect of the two greatly enhances the antibacterial properties of polyethylene composite materials. Due to the difference in their antibacterial mechanisms, the possibility of bacterial resistance can be effectively avoided. At the same time, the combination of chlorogenic acid and talc can effectively protect antibacterial small molecules and prevent the migration of small molecule antibacterial substances when used for a long time in the composite material, thereby making the prepared polyethylene composite material have a long-lasting and efficient antibacterial effect.

[0009] Furthermore, in step S1, the concentration of the silver nitrate solution is 0.2-0.4 mol / L.

[0010] Furthermore, in step S2, the temperature of the heating and stirring is 90-95° C., and the time is 3-5 hours.

[0011] Furthermore, the preparation method of the furan-based silicone rubber comprises the following steps: SS1: Place methyl vinyl silicone rubber in xylene, add glycine and accelerator, heat to 60-65°C for reaction for 5-6h, remove the solvent by rotary evaporation and collect the product to obtain modified silicone rubber; SS2: Place the modified silicone rubber in N,N-dimethylformamide, mix and stir thoroughly, then add glycidyl furfuryl ether and a phase transfer catalyst, heat to 85-95°C and react for 6-8h, remove the solvent by rotary evaporation and collect the product to obtain furan-based silicone rubber.

[0012] In this scheme, under the action of the accelerator, the vinyl group in the structure of methyl vinyl silicone rubber and the amino group in the structure of glycine undergo Michael addition reaction to obtain modified silicone rubber, and then under the action of the phase transfer catalyst, the carboxyl group in the structure of the modified silicone rubber undergoes a ring-opening reaction with the epoxy group in the structure of glycidyl furfuryl ether to obtain furan-based silicone rubber. This furan-based silicone rubber structure contains hydroxyl groups, which interact with the polyethylene composite matrix to enhance compatibility and toughness. At the same time, the organic silicon segments in its structure can effectively enhance the hydrophobicity of the composite material, effectively reduce the bacterial attachment sites, and reduce the possibility of corrosion of the polyethylene composite material due to bacterial physiological activities. The furan group in its structure can effectively enhance the corrosion resistance of the composite material, so that it can stably exist in the corrosive medium, effectively broaden the application field of polyethylene composite materials, and extend the service life.

[0013] Furthermore, in step SS1, the accelerator is triethylamine.

[0014] Furthermore, in step SS2, the phase transfer catalyst is any one of tetrabutylammonium bromide, tetrabutylammonium chloride, and tetrabutylammonium hydroxide.

[0015] Furthermore, the preparation method of the antibacterial polyethylene composite material comprises the following steps: Step 1, polyethylene, maleic anhydride grafted polyethylene, composite antibacterial filler, furan-based silicone rubber, antioxidant, ultraviolet absorber, plasticizer, stabilizer, lubricant are placed in a high-speed mixer, heated to 120-130° C., mixed and stirred for 1-1.5 hours, cooled and discharged to obtain a mixed material; Step 2: Transfer the mixed material to a twin-screw extruder, set the screw speed of the twin-screw extruder to 300-500r / min, the head temperature to 160-165°C, the temperature of zone 1 to 190-195°C, the temperature of zone 2 to 200-205°C, the temperature of zone 3 to 195-200°C, the temperature of zone 4 to 180-185°C, the temperature of zone 5 to 170-175°C, melt-extrude and granulate, and after cooling and shaping, obtain a polyethylene composite material.

[0016] Beneficial effects of the present invention: The present invention prepares composite antibacterial fillers and furan-based silicone rubber in the preparation process of polyethylene composite materials, so that the prepared polyethylene composite materials have excellent antibacterial effect, corrosion resistance, wear resistance and toughness, and have good hydrophobicity, can effectively prevent bacterial erosion, meet the use requirements of medical equipment and food packaging and other fields, and have a long service life.

[0017] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0019] Figure 1 This is a graph showing the sedimentation rates of the silver-loaded talcum powder and the composite antibacterial filler in a dispersion medium. DETAILED DESCRIPTION

[0020] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] The preparation methods of the composite antibacterial filler and furan-based silicone rubber described in the following examples and comparative examples of the present invention are as follows: 1. Preparation of composite antibacterial filler S1: 3 g of talc powder was mixed with 80 ml of 0.2 mol / L silver nitrate solution, and after ultrasonic dispersion for 10 min, the mixture was placed in a reaction kettle, heated to 75°C and stirred for 6 h, and then centrifuged to separate the solid, which was washed and dried to obtain silver-loaded talc powder; S2: 3.2 g of silver-loaded talc was placed in 100 ml of toluene, and after thorough mixing, 2.8 g of chlorogenic acid was added, and the temperature was raised to 90° C. and stirred for 3 h. After filtering, washing, and drying, a composite antibacterial filler was obtained.

[0022] 300 ml of deionized water was used as the dispersion medium, and 3 g of silver-loaded talc and composite antibacterial filler were weighed and placed in it. After ultrasonic dispersion for 20 min, a sedimentation rate test was performed. Figure 1 It can be seen that the sedimentation rate of silver-loaded talc is fast, reaching sedimentation equilibrium within 3 hours; the sedimentation rate of the composite antibacterial filler is relatively slow, reaching sedimentation equilibrium within 8 hours. This is because the silver-loaded talc has not been surface-modified and its dispersibility in the dispersion medium is poor, while the surface of the composite antibacterial filler is modified by organic matter and its dispersibility in the dispersion medium is better, so the sedimentation rate is slower.

[0023] 2. Preparation of furan-based silicone rubber SS1: 3.5 g of methyl vinyl silicone rubber was placed in 60 ml of xylene, 3.3 g of glycine and 0.3 g of triethylamine were added, the temperature was raised to 60 °C for reaction for 5 h, the solvent was removed by rotary evaporation, and the product was collected to obtain modified silicone rubber; The carboxyl content in the modified silicone rubber was tested by acid-base titration. The specific steps are as follows: take 2g of modified silicone rubber as a sample and place it in 60ml acetone solution, add an excess of 0.2mol / L KOH-ethanol standard solution, add 2 drops of phenolphthalein indicator, mix thoroughly, and titrate with 0.2mol / L hydrochloric acid standard solution until the color of the solution changes and no longer changes after continuous stirring for 30 seconds to reach the titration end point. At the same time, do a blank experiment, record the volume of KOH-ethanol standard solution consumed and the volume of hydrochloric acid standard solution, and calculate with reference to the following formula: carboxyl content = 45×c×(V-V0)×100% / m; where 45 is the molar mass of carboxyl, g / mol; c is the concentration of hydrochloric acid standard solution, mol / L; V is the volume of hydrochloric acid standard solution consumed in the sample, ml; V0 is the volume of hydrochloric acid standard solution consumed in the blank sample, ml; m is the sample mass, g; after calculation, the carboxyl content in the sample is 8.67%.

[0024] SS2: Place 3.8 g of modified silicone rubber in 80 ml of N,N-dimethylformamide, mix and stir thoroughly, then add 3 g of glycidyl furfuryl ether and 0.1 g of tetrabutylammonium bromide, heat to 85 °C and react for 6 h. After rotary evaporation to remove the solvent, collect the product to obtain furan-based silicone rubber.

[0025] The carboxyl content in the furan-based silicone rubber was tested by acid-base titration. The specific test results were the same as those in step SS1. After calculation, the carboxyl content in the furan-based silicone rubber was 0.9%. Compared with the carboxyl content in the modified silicone rubber, the carboxyl content in the furan-based silicone rubber was greatly reduced. This was due to the ring-opening reaction between the carboxyl groups in the modified silicone rubber structure and the epoxy groups in the glycidyl furfuryl ether structure, resulting in consumption. Example

[0026] Preparation of polyethylene composites Step 1, put 60 parts of polyethylene, 20 parts of maleic anhydride grafted polyethylene, 8 parts of composite antibacterial filler, 12 parts of furan-based silicone rubber, 2 parts of antioxidant 1010, 1 part of ultraviolet absorber UV-1577, 1 part of diisononyl phthalate, 2 parts of calcium zinc stabilizer, and 3 parts of paraffin into a high-speed mixer, heat to 120° C. and mix and stir for 1 hour, cool and discharge to obtain a mixed material; Step 2: Transfer the mixed material to a twin-screw extruder, set the screw speed of the twin-screw extruder to 300 r / min, the head temperature to 160°C, the temperature of zone 1 to 190°C, the temperature of zone 2 to 200°C, the temperature of zone 3 to 195°C, the temperature of zone 4 to 180°C, the temperature of zone 5 to 170°C, melt-extrude and granulate, and after cooling and shaping, obtain a polyethylene composite material. Example

[0027] Preparation of polyethylene composites Step 1, 70 parts of polyethylene, 23 parts of maleic anhydride grafted polyethylene, 9 parts of composite antibacterial filler, 13 parts of furan-based silicone rubber, 2.5 parts of antioxidant 1135, 1.5 parts of ultraviolet absorber UV-2908, 2 parts of dioctyl phthalate, 3 parts of barium zinc stabilizer, and 4 parts of polyethylene wax are placed in a high-speed mixer, heated to 125° C. and mixed and stirred for 1.2 hours, cooled and discharged to obtain a mixed material; Step 2: Transfer the mixed material to a twin-screw extruder, set the screw speed of the twin-screw extruder to 400 r / min, the head temperature to 163°C, the temperature of zone 1 to 193°C, the temperature of zone 2 to 203°C, the temperature of zone 3 to 198°C, the temperature of zone 4 to 183°C, the temperature of zone 5 to 173°C, melt-extrude and granulate, and after cooling and shaping, obtain a polyethylene composite material. Example

[0028] Preparation of polyethylene composites Step 1, put 80 parts of polyethylene, 25 parts of maleic anhydride grafted polyethylene, 10 parts of composite antibacterial filler, 15 parts of furan-based silicone rubber, 3 parts of antioxidant 5057, 2 parts of ultraviolet absorber 1130, 3 parts of dimethyl phthalate, 4 parts of calcium zinc stabilizer, and 5 parts of paraffin into a high-speed mixer, heat to 130° C. and mix and stir for 1.5 hours, cool and discharge to obtain a mixed material; Step 2: Transfer the mixed material to a twin-screw extruder, set the screw speed of the twin-screw extruder to 500 r / min, the head temperature to 165°C, the temperature of zone 1 to 195°C, the temperature of zone 2 to 205°C, the temperature of zone 3 to 200°C, the temperature of zone 4 to 185°C, the temperature of zone 5 to 175°C, melt-extrude and granulate, and after cooling and shaping, obtain a polyethylene composite material.

[0029] Comparative Example 1 Preparation of polyethylene composites Step 1, 70 parts of polyethylene, 23 parts of maleic anhydride grafted polyethylene, 13 parts of furan-based silicone rubber, 2.5 parts of antioxidant 1135, 1.5 parts of ultraviolet absorber UV-2908, 2 parts of dioctyl phthalate, 3 parts of barium zinc stabilizer, and 4 parts of polyethylene wax are placed in a high-speed mixer, heated to 125° C. and mixed and stirred for 1.2 hours, cooled and discharged to obtain a mixed material; Step 2: Transfer the mixed material to a twin-screw extruder, set the screw speed of the twin-screw extruder to 400 r / min, the head temperature to 163°C, the temperature of zone 1 to 193°C, the temperature of zone 2 to 203°C, the temperature of zone 3 to 198°C, the temperature of zone 4 to 183°C, the temperature of zone 5 to 173°C, melt-extrude and granulate, and after cooling and shaping, obtain a polyethylene composite material.

[0030] Comparative Example 2 Preparation of polyethylene composites Step 1, 70 parts of polyethylene, 23 parts of maleic anhydride grafted polyethylene, 9 parts of composite antibacterial filler, 2.5 parts of antioxidant 1135, 1.5 parts of ultraviolet absorber UV-2908, 2 parts of dioctyl phthalate, 3 parts of barium zinc stabilizer, and 4 parts of polyethylene wax are placed in a high-speed mixer, heated to 125° C. and mixed and stirred for 1.2 hours, cooled and discharged to obtain a mixed material; Step 2: Transfer the mixed material to a twin-screw extruder, set the screw speed of the twin-screw extruder to 400 r / min, the head temperature to 163°C, the temperature of zone 1 to 193°C, the temperature of zone 2 to 203°C, the temperature of zone 3 to 198°C, the temperature of zone 4 to 183°C, the temperature of zone 5 to 173°C, melt-extrude and granulate, and after cooling and shaping, obtain a polyethylene composite material.

[0031] Comparative Example 3 Preparation of polyethylene composites Step 1, 70 parts of polyethylene, 23 parts of maleic anhydride grafted polyethylene, 9 parts of silver-loaded talc, 13 parts of furan-based silicone rubber, 2.5 parts of antioxidant 1135, 1.5 parts of ultraviolet absorber UV-2908, 2 parts of dioctyl phthalate, 3 parts of barium zinc stabilizer, and 4 parts of polyethylene wax are placed in a high-speed mixer, heated to 125° C. and mixed and stirred for 1.2 hours, cooled and discharged to obtain a mixed material; Step 2: Transfer the mixed material to a twin-screw extruder, set the screw speed of the twin-screw extruder to 400 r / min, the head temperature to 163°C, the temperature of zone 1 to 193°C, the temperature of zone 2 to 203°C, the temperature of zone 3 to 198°C, the temperature of zone 4 to 183°C, the temperature of zone 5 to 173°C, melt-extrude and granulate, and after cooling and shaping, obtain a polyethylene composite material.

[0032] Comparative Example 4 Preparation of polyethylene composites Step 1, 70 parts of polyethylene, 23 parts of maleic anhydride grafted polyethylene, 9 parts of composite antibacterial filler, 13 parts of methyl vinyl silicone rubber, 2.5 parts of antioxidant 1135, 1.5 parts of ultraviolet absorber UV-2908, 2 parts of dioctyl phthalate, 3 parts of barium zinc stabilizer, and 4 parts of polyethylene wax are placed in a high-speed mixer, heated to 125° C. and mixed and stirred for 1.2 hours, cooled and discharged to obtain a mixed material; Step 2: Transfer the mixed material to a twin-screw extruder, set the screw speed of the twin-screw extruder to 400 r / min, the head temperature to 163°C, the temperature of zone 1 to 193°C, the temperature of zone 2 to 203°C, the temperature of zone 3 to 198°C, the temperature of zone 4 to 183°C, the temperature of zone 5 to 173°C, melt-extrude and granulate, and after cooling and shaping, obtain a polyethylene composite material.

[0033] Performance Testing The polyethylene composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were made into samples that met the specifications, and the antibacterial properties of the samples were tested with reference to the standard GB / T31402-2015; the bending elastic modulus of the samples was tested with reference to the standard GB / T9341-2008; the samples were placed in a hydrochloric acid solution with a concentration of 1 mol / L and a sodium hydroxide solution with a concentration of 1 mol / L for 24 hours, and the weight loss of the samples was counted to determine the corrosion resistance of the samples; the samples were placed on the sample table of a GSL-46 steel wool abrasion tester, and a 1000g load weight was prevented. The sample surface was rubbed back and forth at a rate of 15 mm / s, and repeated 50 cycles. The scratches on the sample surface were observed, and the wear resistance of the samples was tested; the water contact angle of the samples was tested using a JC2000D2G contact angle tester to determine the hydrophobicity of the samples; the specific test results are shown in the following table:

[0034] As can be seen from the above table, the samples prepared in Examples 1 to 3 all have excellent antibacterial properties, toughness, corrosion resistance, wear resistance and hydrophobic effect. In the sample prepared in Comparative Example 1, no composite antibacterial filler was added, and the antibacterial and wear resistance were poor. In the sample prepared in Comparative Example 2, no furan-based silicone rubber was added, and the corrosion resistance and hydrophobicity were poor. In the sample prepared in Comparative Example 3, the antibacterial and corrosion resistance of silver-loaded talc powder was directly added, and the poor wear resistance was caused by slight agglomeration of the silver-loaded talc powder that had not been surface-modified. In the sample prepared in Comparative Example 4, methyl vinyl silicone rubber was directly added, and the compatibility with the matrix material needs to be improved, so the hydrophobic effect is not as good as that of the embodiment, and because the furan group with anti-corrosion ability is not introduced into its structure, the anti-corrosion ability is general.

[0035] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0036] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. An antibacterial polyethylene composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 60-80 parts of polyethylene, 20-25 parts of maleic anhydride grafted polyethylene, 8-10 parts of composite antibacterial filler, 12-15 parts of furan-based silicone rubber, 2-3 parts of antioxidant, 1-2 parts of ultraviolet absorber, 1-3 parts of plasticizer, 2-4 parts of stabilizer and 3-5 parts of lubricant.

2. The antibacterial polyethylene composite material according to claim 1, characterized in that: The antioxidant is any one of antioxidant 1010, antioxidant 1135, and antioxidant 5057; the ultraviolet absorber is any one of ultraviolet absorber UV-1577, ultraviolet absorber 1130, and ultraviolet absorber UV-2908; the plasticizer is any one of diisononyl phthalate, dioctyl phthalate, dimethyl phthalate, and epoxy soybean oil; the stabilizer is any one of calcium zinc stabilizer and barium zinc stabilizer; the lubricant is any one of paraffin wax and polyethylene wax.

3. The antibacterial polyethylene composite material according to claim 1, characterized in that: The preparation method of the composite antibacterial filler comprises the following steps: S1: talcum powder is mixed with silver nitrate solution, ultrasonically dispersed for 10-15 minutes, placed in a reaction kettle, heated to 75-85°C, stirred for 6-8 hours, centrifuged to separate the solid, washed and dried to obtain silver-loaded talcum powder; S2: silver-loaded talc powder is placed in toluene, mixed thoroughly, and then chlorogenic acid is added. The mixture is heated and stirred, filtered, washed, and dried to obtain a composite antibacterial filler.

4. The antibacterial polyethylene composite material according to claim 3, characterized in that: In step S1, the concentration of the silver nitrate solution is 0.2-0.4 mol / L.

5. The antibacterial polyethylene composite material according to claim 3, characterized in that: In step S2, the temperature of the heating and stirring is 90-95° C. and the time is 3-5 hours.

6. The antibacterial polyethylene composite material according to claim 1, characterized in that: The preparation method of the furan-based silicone rubber comprises the following steps: SS1: Place methyl vinyl silicone rubber in xylene, add glycine and accelerator, heat to 60-65°C for reaction for 5-6h, remove the solvent by rotary evaporation and collect the product to obtain modified silicone rubber; SS2: Place the modified silicone rubber in N,N-dimethylformamide, mix and stir thoroughly, then add glycidyl furfuryl ether and a phase transfer catalyst, heat to 85-95°C and react for 6-8h, remove the solvent by rotary evaporation and collect the product to obtain furan-based silicone rubber.

7. The antibacterial polyethylene composite material according to claim 6, characterized in that: In step SS1, the accelerator is triethylamine.

8. The antibacterial polyethylene composite material according to claim 6, characterized in that: In step SS2, the phase transfer catalyst is any one of tetrabutylammonium bromide, tetrabutylammonium chloride, and tetrabutylammonium hydroxide.

9. The antibacterial polyethylene composite material according to claim 1, characterized in that: The preparation method of the antibacterial polyethylene composite material comprises the following steps: Step 1, polyethylene, maleic anhydride grafted polyethylene, composite antibacterial filler, furan-based silicone rubber, antioxidant, ultraviolet absorber, plasticizer, stabilizer, lubricant are placed in a high-speed mixer, heated to 120-130° C., mixed and stirred for 1-1.5 hours, cooled and discharged to obtain a mixed material; Step 2: Transfer the mixed material to a twin-screw extruder, set the screw speed of the twin-screw extruder to 300-500r / min, the head temperature to 160-165°C, the temperature of zone 1 to 190-195°C, the temperature of zone 2 to 200-205°C, the temperature of zone 3 to 195-200°C, the temperature of zone 4 to 180-185°C, the temperature of zone 5 to 170-175°C, melt-extrude and granulate, and after cooling and shaping, obtain a polyethylene composite material.

Citation Information

Patent Citations

  • Crosslinked polyethylene composite material and preparation method thereof

    CN101948583B

  • Antibacterial thermoplastic plastic composition and preparation method thereof

    CN103073907A

  • Composite drainage network material and preparation method thereof

    CN119161652A

Cited By

  • Antibacterial polyethylene composite material and preparation method thereof

    CN120383786A

  • High-temperature-resistant functional food preservation bag and manufacturing method thereof

    CN121378932A